Analisis Struktur Modal Konservatif terhadap Optimalisasi Return on Equity: Studi Kasus PT Campina Ice Cream Industry, Tbk (2020-2024) - Aryani Sri Ramadhani; Euis Novianty Lana; Sri Retnaning Sampurnaningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Conservative capital structure is a strategy focused on internal funding stability, which theoretically may limit the scope for optimizing shareholder returns. This study aims to analyze the optimization strategy of Return on Equity (ROE) at PT Campina Ice Cream Industry, Tbk during the 2020–2024 period under a conservative capital structure. The methodology employed is quantitative descriptive using financial ratio analysis and the DuPont Analysis approach. The results indicate that PT Campina maintains a very safe capital structure with a Debt to Equity Ratio (DER) of 0.1–0.2 times and a Debt to Asset Ratio (DAR) between 10.5%–13.7%. Low debt levels result in a low Equity Multiplier (1.11–1.16), shifting the burden of ROE optimization entirely onto net profit efficiency and asset productivity. ROE reached an optimal peak of 13.41% in 2023, driven by the highest Net Profit Margin (NPM) of 11.22%. However, in 2024, ROE declined to 10.43% due to operating expense pressures that pushed the NPM down to 8.38%. These findings confirm that under a conservative capital structure, ROE is highly vulnerable to fluctuations in operating costs. The primary recommended strategy is the careful control of operating expenses to enhance profit margins.